2009
DOI: 10.1530/rep-08-0514
|View full text |Cite
|
Sign up to set email alerts
|

Redox control of surface protein sulphhydryls in bovine spermatozoa reversibly modulates sperm adhesion to the oviductal epithelium and capacitation

Abstract: Oviductal fluid molecules, such as sulphated glycosaminoglycans and disulphide-reductants, may represent periovulatory signals for the release of spermatozoa from the oviductal reservoir in the bovine species. Disulphide-reductants release spermatozoa through the reduction of sperm-surface disulphides to sulphhydryls (SH). Herein, we studied sperm-surface protein SH through labelling with maleimidylpropionyl biocytin in the initial sperm suspension, in the subpopulations able and unable to adhere to the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…PEN, and other thiols (compounds with a sulfhydryl group), have been shown to initiate sperm release through the reduction of sperm surface disulfides to sulfhydryls (Talevi et al 2007, Gualtieri et al 2009. It is probable that PEN may prevent or revert sperm association by the reduction of disulphide bonds of a sperm protein, which are required for sperm binding, to free sulfhydryls.…”
Section: Discussionmentioning
confidence: 99%
“…PEN, and other thiols (compounds with a sulfhydryl group), have been shown to initiate sperm release through the reduction of sperm surface disulfides to sulfhydryls (Talevi et al 2007, Gualtieri et al 2009. It is probable that PEN may prevent or revert sperm association by the reduction of disulphide bonds of a sperm protein, which are required for sperm binding, to free sulfhydryls.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, BSP homologs were found in the human (BSPH1) and mouse (32). It has also been suggested that the reducing redox environment of the oviduct could promote the release of sperm by facilitating the reduction of cell surface thiols on sperm cell proteins important for sperm-oviduct binding (33).…”
Section: Sperm Migration In the Female Reproductive Tractmentioning
confidence: 99%
“…Both release inducers act on spermatozoa and trigger capacitation-related changes (Gualtieri et al 2005, Talevi et al 2007. Although both inducers trigger capacitation, we showed that only spermatozoa capacitated by penicillamine are able to revert this process (Gualtieri et al 2009). Interestingly, CB1 was not detectable in heparin-released spermatozoa by both immunocytochemistry and western blot analysis, whereas, in spermatozoa released by penicillamine, CB1 had the same immunolocalization observed in the initial sperm population.…”
Section: Sperm-oviduct Interactionmentioning
confidence: 68%
“…At the end of coincubation, unbound spermatozoa were removed by extensive washings with TALP, and cocultures were fixed to quantify the number of adhering spermatozoa as previously described (Gualtieri et al 2009). To detect the effect of AEA on spermoviduct release, explants were inseminated in TALP as above, and after unbound sperm removal, cocultures were treated with AEA 2 nM, 5 mM, or TALP alone, and analyzed.…”
Section: Effect Of Aea On Sperm-oviduct Interactionmentioning
confidence: 99%